ANALYSIS OF MARRIAGE LAW THROUGH MOBILE TELEPHONE COMMUNICATION DEVICES FROM THE PERSPECTIVE OF ISLAMIC LAW - Tatang (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Marriage from an Islamic legal perspective through mobile phone communication is a new issue, as there is no standard fiqh book on this matter. The validity of marriage through telecommunications does not yet have its own legal status because the Marriage Law 1 of 1974 does not regulate the law of prenuptial agreements. Legal analysis of the Islamic legal concept of marriage through telecommunications requires a search for law ( rechtsvinding ) by judges as conservative parties. Even in lawless environments, there are attempts to violate or break well-enforced rules and regulations. Efforts to interpret existing law properly can be applied in all future cases, because the law is sometimes unclear, incomplete, or not up-to-date ( rechtsvinding ). In other words, judges must adapt the law to more serious cases, because existing law cannot cover all social phenomena.